2016
DOI: 10.4103/2141-9248.181839
|View full text |Cite
|
Sign up to set email alerts
|

Median nerve conduction in healthy Nigerians: Normative data

Abstract: Background:Because of lack of local normative data, electrodiagnostic laboratories in Nigeria apply standard values generated in the USA and Europe to diagnose different median nerve abnormalities.Aim:To develop normative values for motor and sensory median nerve conduction studies (NCSs) in Nigerian population.Subjects and Methods:In a cross-sectional study design, a total of 200 healthy volunteers were selected after clinical evaluation to exclude systemic or neuromuscular disorders. NCS of the median nerves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This could be elicited from the work of Takano et al 37 who found that shorter persons have statically significant fast conduction velocity than taller persons. 38 The current study showed that age was also found to influence nerve conduction velocity of the median sensory fibers; as a negative correlation; so that with increasing age; the nerve conduction velocity declines, a finding that collaborates with literature and with Farqad et al, 20 Thakuer et al 22 who further added that age has definite inverse effects on amplitude and duration of motor and sensory nerves signals, a finding that was reestablished by Owolabi LF et al 39 and Letz R et al 40 Our results disagree with Amatya and Khanal 41 who revealed that no significant correlations of NCVs with age, height, weight, and body mass index.…”
Section: Discussionsupporting
confidence: 82%
“…This could be elicited from the work of Takano et al 37 who found that shorter persons have statically significant fast conduction velocity than taller persons. 38 The current study showed that age was also found to influence nerve conduction velocity of the median sensory fibers; as a negative correlation; so that with increasing age; the nerve conduction velocity declines, a finding that collaborates with literature and with Farqad et al, 20 Thakuer et al 22 who further added that age has definite inverse effects on amplitude and duration of motor and sensory nerves signals, a finding that was reestablished by Owolabi LF et al 39 and Letz R et al 40 Our results disagree with Amatya and Khanal 41 who revealed that no significant correlations of NCVs with age, height, weight, and body mass index.…”
Section: Discussionsupporting
confidence: 82%
“…There is evidence to suggest that nerve conduction slows down with advancing age. [ 3 22 25 27 28 ] Therefore, while the present study was confined to a narrow age group (17–21 years), most of the other researchers had included a large age group (including elderly population) which might have led to the increase in latency values with consequent reduction of the velocity values in their participants, thereby creating discrepancies between their results and our own. Another major reason for the observed differences is that since most of the available studies are western, hence the consequent methodology and geographical differences as well as the variations in the lifestyle, dietary, and morphological characteristics of study participants might also have influenced the study results.…”
Section: Discussionmentioning
confidence: 90%
“…[ 1 3 4 5 6 ] It is often most desirable and encouraged in a clinical setting to have reference values that are derived from the same population or from a sample population that approximates, as closely as possible, the demographic characteristics of the patient being tested. [ 3 ] The few reports available on NCS normative values from Nigeria were focused on median[ 7 ] and sural nerves,[ 8 ] but there is no published account on ulnar nerves in the country.…”
Section: Introductionmentioning
confidence: 99%